The development of theology at Stellenbosch from 1859-1919 - Thom, Gideon (Rhodes University, Faculty of Divinity, Department of Divinity, 1990)
This study seeks to give an exposition of the development of theology at the Stellenbosch Kweekskool from 1859 until 1919, a period that coincided with the formative years of Afrikaner nationalism. John Murray (1826-1882) was nurtured in evangelical Calvinism but received his theological training in 'moderate' Utrecht. As Calvinist he emphasized salvation by grace and Christian obedience, as evangelical, union with Christ, and as kenoticist he emphasized the relevance of the humanity of Christ. N.J. Hofmeyr (1827-1909) was converted under an evangelical Lutheran and received his training in Utrecht, in the heyday of Dutch ethical and German mediating theology. He was fascinated by the historical Jesus. In his view, the 'religion of Jesus' was not the moralistic one imagined by the modernists, but an experience of sonship, continually challenged by severe temptations. The central theme of his theology was the huiothesia, the sonship of Jesus being the prototype of our sonship. As he was the spiritual father of many generations of Stellenbosch students, his Christocentric emphasis and his doctrine of huiothesia played an important role in the development of NGK spirituality. Other themes in Hofmeyr's theology bore the marks of mediating theology: The idea that the conscience is the voice of God, the 'natural' compatibility between the human and the divine, the importance of experience in the theological enterprise and the idea that grace must accommodate itself to nature. J.I. Marais (1848-1919) and P.J.G. de Vos (1842-1931), who received part of their training in Scotland, were more conservative in theology than Hofmeyr. By the turn of the century De Vos has fully accepted scholastic Calvinism and premillenniaIism; Marais accepted premillennialism around 1914. The experiences of the Anglo-Boer War precipitated the close relationship between the Afrikaner and the NGK, and the lack of a strong doctrine of the church in Stellenbosch theology added to the blurring of distinctions between church and people. The national church of the Scots and Dutch traditions became the volkskerk of the Afrikaner. Important biblical dimensions of Murray and Hofmeyr's theology were neglected after Hofmeyr's death. The conviction that God revealed himself completely in the human Christ was weakened by fundamentalism and the tendency to see God's will in the history of the volk. Their eschatology - which expected great success for the gospel - was replaced by premillennialism, which expected only limited success for missions before the parousia. Hofmeyr's social gospel, which was applied to the problem of the 'poor whites', was gradually replaced by a negative view of the social relevance of the gospel, especially in racial matters. This gradual change of theological direction involved a growing sympathy with fundamentalism and Kuyperianism, but did not consist in a full revival of reformation theology
Keywords: Nederduitse Gereformeerde Kerk; Stellenbosch Theological Seminary